Migration From A Relational Database To A Document-Oriented Database Based On Document-Oriented Data Schema - M S, Hamouda Shady (2020)
Big data is a crucial issue that has emerged as one of the most important technologies in the modern world. Most studies have highlighted the inability of a relational database to handle big data. This challenge has led to the presentation of the “not only structured query language (NoSQL) database” as a new concept of database technology. One of the most powerful types of NoSQL databases is the document-oriented database that supports a flexible schema and store data in a semi-structured format. Recently, many researchers have migrated from relational databases to document-oriented databases because of scalability, availability, and performance. However, their migration methods are facing three issues; the first issue is that there are no specifications that can be recognized to define a schema for a document-oriented database, and second, there is no method to normalize or de-normalize data in order to implement the embedded and reference document. The third is the migration from the relational database to a document-oriented database does not consider all the properties of the former, especially on how to handle various types of relationships. This study proposed a methodology to handle the migration issues through three phases: first, design a document-oriented data schema (DODS) based on the entity-relational (ER) model; second, enhance transformation rules to map the entity relational schema to the document-oriented data schema based on normalization and de-normalization data; third, migrate a relational database to a document-oriented database.